2016
DOI: 10.1002/ijc.30505
|View full text |Cite
|
Sign up to set email alerts
|

Antiglioma effects of N6‐isopentenyladenosine, an endogenous isoprenoid end product, through the downregulation of epidermal growth factor receptor

Abstract: Malignant gliomas are highly dependent on the isoprenoid pathway for the synthesis of lipid moieties critical for cell proliferation. The isoprenoid derivative N6-isopentenyladenosine (iPA) displays pleiotropic biological effects, including a direct anti-tumor activity in several tumor models. The antiglioma effects of iPA was then explored in U87MG cells both in vitro and grafted in mice and the related molecular mechanism confirmed in primary derived patients' glioma cells. iPA powerfully inhibited tumor cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 48 publications
2
43
0
Order By: Relevance
“…We have demonstrated that the modified adenosine compound i6A exerts cytotoxic, antiangiogenic and proapoptotic activity in different cell lines (Laezza et al, ; Spinola et al, ; Laezza et al, ; Laezza et al, ; Pisanti et al, ; Ciaglia et al, ). Earlier reports by our group highlighted the involvement of FPPS in i6A action in different physiopathological settings (Laezza et al, ; Ciaglia et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated that the modified adenosine compound i6A exerts cytotoxic, antiangiogenic and proapoptotic activity in different cell lines (Laezza et al, ; Spinola et al, ; Laezza et al, ; Laezza et al, ; Pisanti et al, ; Ciaglia et al, ). Earlier reports by our group highlighted the involvement of FPPS in i6A action in different physiopathological settings (Laezza et al, ; Ciaglia et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It belongs to the cytokinin family, involved in control of many processes in plants (Kersten, ; Laten and Zahareasdoktor, ; Bifulco et al, ). In humans, many biological actions, both in vitro and in vivo , including antitumour effects, have been attributed to i6A (Woo et al, ; Castiglioni et al, ; Laezza et al, ; Pisanti et al, ; Laezza et al, ; Ciaglia et al, ). Interest in the study of this compound has been reinforced by experimental observations that i6A interferes with the growth of k‐ras transformed thyroid cells (KiMol) xenograft tumours by inhibiting the expression and activity of farnesyl pyrophosphate synthase (FPPS) (Laezza et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…We and others have previously reported cytotoxic, antiangiogenic and proapoptotic activity of iPA in different cell lines . Recently, a surprising antiglioma effect was also documented in vitro and in vivo model, where the isoprenoide derivative act through the specific degradation of EGFR and downregulation of cell signaling pathways dependent from the growth factor receptor oncogene.…”
Section: Discussionmentioning
confidence: 79%
“…The patients had been informed about the establishment of cellular models from their tumor and had given informed consent in written form. The preparation of adherent primary cultures of brain tumor cells (designated as GBMn) was conducted as reported elsewhere …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation